Clinical and genetic characteristics of 36 children with Joubert syndrome - Dong, Yan; Zhang, Ke; Yao, He; Jia, Tianming; Wang, Jun; Zhu, Dengna; Xu, Falin; Cheng, Meiying; Zhao, Shichao; Shi, Xiaoyi (Frontiers in Pediatrics, 2023)
Background and Aims: Joubert syndrome (JBTS, OMIM # 213300) is a group of ciliopathies characterized by mid-hindbrain malformation, developmental delay, hypotonia, oculomotor apraxia, and breathing abnormalities. The study aimed to summarize clinical manifestations, particular appearance on cranial imaging, genetic data, and prognostic features of patients with JBTS.Methods: A retrospective case review of 36 cases of JBTS from May 1986 to December 2021 was performed. Clinical data of JBTS patients with development retardation and molar tooth sign on cranial imaging as the main features were analyzed.Genetic testing was performed according to consent obtained from patients and their families. The Gesell Developmental Scale was used to evaluate the intelligence level before and after treatment. The children were divided into a purely neurological JBTS (pure JBTS) group and JBTS with multi-organ system involvement group and then followed up every 3-6 months.We enrolled 18 males and 18 females. Thirty-four (94.44%) cases had developmental delay, one patient (2.78%) had strabismus, and one patient (2.78%) had intermittent dizziness. There was one case co-morbid with Lesch-Nyhan syndrome. Three-quarters of cases had one or more other organ or system involvement, with a greater predilection for vision and hearing impairment. JBTS could also involve the skin. Thirty-one cases (86.11%) showed a typical molar tooth sign, and five cases showed a bat wing sign on cranial imaging. We found six JBTS-related novel gene loci variants: C5orf42: c.4189+1G>A, c.3101T>C(p.Ile1034Thr), c.3733T>C (p.Cys1245Arg), c.4080G>A(p.Lys1360=); RPGRIP1L: c.1351-11A>G; CEP120: c.214 C>T(p.Arg72Cys). The CHD7 gene may be potentially related to the occurrence of JBTS. Analysis showed that the prognosis of pure JBTS was better than that of JBTS with neurological and non-neurological involvement after the formal rehabilitation treatment (P < 0.05). Our findings indicate that early cranial imaging is helpful for the etiological diagnosis of children with unexplained developmental delay and multiple malformations. Patients with JBTS may have coexisting skin abnormalities. The novel gene loci of C5orf42, RPGRIP1L, and CEP120 were associated with JBTS in our study and provided significant information to enrich the related genetic data. The prognosis of children with pure JBTS is better than JBTS children with non-neurological involvement.